Ten Crises The Political Economy of China's Development (1949-2020) - Wen, Tiejun (Global University for Sustainability Book Series, 2021)
This open access book contextualizes China's 70 years of contemporary history against one coherent backdrop: a late developing country endeavoring at all costs to industrialize, whether it was in the name of socialism or capitalism. This path is even more complicated by China's getting caught in the geo-political confrontation of two superpowers in the 20th century: the Soviet Union and the USA. The author argues that China could only cope with these costs by internalizing them. As one of the leading scholars of agrarian issues in China, the author emphasizes the role of rural sector having been a source of surplus extraction for industrialization and the receptor of cost of development being transferred by the urban sector. This book is the first volume of the Global University for Sustainability Book Series published with Palgrave Macmillan.